The Effect of Growing Media Composition and Indole–3–Butyric Acid Concentration on Growth and Flowering Time of Rose Cuttings - Muhaimin Ar Rasyid; Karno Karno; Rosyida Rosyida (Jurnal Ilmu Pertanian Indonesia, 2025)
The purpose of this study is to increase the propagation success rate of Rosa centifolia L. cuttings by examining the interaction of several types of growing media with varying amounts of auxin-based plant growth regulators. A factorial Completely Randomized Design with four treatment groups and three replications. The first factor was the composition of the planting media, which was made up of four tiers of soil: soil:husk (1:1), soil:compost (1:1), and soil:manure (1:1). The second factor was the concentration of indole-3-butyric acid (IBA), which has four levels: Z1 (control), Z2 (500 ppm), Z3 (1000 ppm), and Z4 (1500 ppm). The acquired data were subjected to Analysis of Variance, which was followed by a comparison using the Least Significant Difference test to identify significant treatment effects. The results showed that the soil:compost (1:1) treatment was the most effective planting media composition in terms of shoot length, number of leaves, and flowering time. Providing auxin concentrations is not effective in increasing root growth and rose plant yield through cutting propagation. Keywords: auxin, flower appearance time, growing media, indole–3–butyric acid, rose cuttings